Penguatan Financial Performance dan Poverty Reduction Melalui Literasi Keuangan di Industri Keuangan Non Bank (IKNB) Syariah pada Masyarakat Jawa Tengah - Joko Robi Prasetyo; Supriyanto Supriyanto; Budi Sukardi (Journal of Finance and Islamic Banking, 2019)
This study aims to analyze the effect of accessibility directly on financial performance, the effect of indirect accessibility on financial performance through poverty reduction, the effect of direct availability on financial performance, the effect of indirect availability on financial performance through poverty reduction, the effect of direct usefulness on financial performance, the effect of indirect use on financial performance through poverty reduction, the effect of financial performance directly on poverty reduction. This research was conducted in the Islamic non-bank financial industry (IKNB) in the Central Java region which is incorporated in the OJK Sharia Financial Statements and Central Java BPS Reports. The results of the study are accessibility does not directly affect financial performance (p.0,318> 0.05). Availability does not directly affect financial performance, this is evidenced by the statistical t value (p.0,605> 0.05). Usability does not directly affect financial performance, this is evidenced by the statistical t value (p.0,456> 0.05). Financial performance does not directly affect poverty reduction, this is evidenced by the statistical t value (p.0,153> 0.05).